2015
DOI: 10.1021/acs.jpcc.5b10130
|View full text |Cite
|
Sign up to set email alerts
|

DFT Study of CO2 Activation on Doped and Ultrathin MgO Films.

Abstract: The bonding mode of carbon dioxide with the surface of various forms of MgO has been investigated by means of density functional theory calculations. Four supports have been considered: the bare MgO(100) surface, the surface of Al-doped MgO, and ultrathin MgO/Ag(100) and MgO/Mo(100) films. Three forms of adsorbed CO2 have been investigated: physisorbed CO2, chemisorbed carboxylate, CO2 –, and carbonate, CO3 2–. While on MgO(100) CO2 forms either the physisorbed species or the more stable surface carbonate, on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 59 publications
0
24
0
Order By: Relevance
“…25 For CO 2 on MgO(001), it has been shown that electron transfer from subsurface Mo can affect the preferred binding of CO 2 as surface carboxylate rather than carbonate. 26,27 In this combined experimental and theoretical study, we report on CO 2 adsorption on well-characterized CaO thin films grown on metal substrates, focusing on the initial stages of adsorption in the low coverage regime. Using infrared reflection-absorption spectroscopy (IRAS), temperature programmed desorption (TPD), microcalorimetry, and quantum chemistry calculations, we show that CO 2 strongly adsorbs as monodentate carbonates first on step edges, followed by terrace sites.…”
Section: Introductionmentioning
confidence: 99%
“…25 For CO 2 on MgO(001), it has been shown that electron transfer from subsurface Mo can affect the preferred binding of CO 2 as surface carboxylate rather than carbonate. 26,27 In this combined experimental and theoretical study, we report on CO 2 adsorption on well-characterized CaO thin films grown on metal substrates, focusing on the initial stages of adsorption in the low coverage regime. Using infrared reflection-absorption spectroscopy (IRAS), temperature programmed desorption (TPD), microcalorimetry, and quantum chemistry calculations, we show that CO 2 strongly adsorbs as monodentate carbonates first on step edges, followed by terrace sites.…”
Section: Introductionmentioning
confidence: 99%
“…For ionic oxides, such as MgO, or ZrO 2 , H 2 dissociation occurs preferentially via heterolytic splitting, forming an hydroxyl O 2− H + group and hydride M n+ H − group (M is the metal cation). On the other hand, H 2 prefers to dissociate homolytically on reducible oxide, such as TiO 2 , CeO 2 forming two O 2− H + groups and two extra electrons usually localized in the d states of neighboring transition metal atoms. Sometimes, the electronic properties of an oxide can be completely changed when this is obtained in nanostructured form, either free‐standing ultrathin films, ultrathin films deposited on metal supports, or simply oxide nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…On metal oxide surfaces, the dissociation of H 2 is mostly depending on the nature of the oxide. For ionic oxides, such as MgO, [33,34] or ZrO 2 , [35,36] [37] CeO 2 [38] forming two O 2À H + groups and two extra electrons usually localized in the d states of neighboring transition metal atoms. Sometimes, the electronic properties of an oxide can be completely changed when this is obtained in nanostructured form, either free-standing ultrathin films, ultrathin films deposited on metal supports, or simply oxide nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to theoretical and experimental advantages, MgO surfaces have become a prototypical model system for detailed investigations of different features in catalysis such as basicity testing, charge transfer, CO 2 activation, and H 2 O dissociation on simple doped or thin film MgO. [1][2][3][4][5][6][7] The presence of hydrogen on solid surfaces is of key importance for several processes like heterogeneous catalysis, hydrogen storage fuel cells, and sensors. [8][9][10] Understanding the adsorption of hydrogen is important for various processes such as the dissociation/recombination of hydrogen, direct X-H dissociation of molecules (e.g.…”
Section: Introductionmentioning
confidence: 99%